(3ef MUGO GdCjGe(B- (3GdLRA GdChd(B/ s - Nasrallah, Emily (3fUQGddg, Eedjs ((3HjQhJ; s Naufal- Hachette Antoine; (3fhad (B- (3gGTjJ CfWhGfs, 2012)
Title in French: Au fil de la moisson des jours. Tome 1. By Emily Nasrallah (3LRA Cqhd ef KdGKI, jQqcR Ydi GdeQCI, CkqeG hCOjHI hSqjOI efRd hYGedI, ebjeI hegGLQI, hgj aj cqd MGdGJgG, hGgHI GdMjGI hMGQSJgG, heY Pdc jMGhd GdHYV EScGJgG hbgQgG hMQeGfgG hJYfjagG, hgj UGHQI eKGHQI, dCqf zeaGJjM GdMjGIy oCYWjJ dgG Ohf ShGgG, hgj ndpfYe GdMGaXI GdCejfI (BPart one of three focuses on women, as mothers, writers, homemakers, workers, both residents and immigrants, in all their roles as givers and guardians of life. Despite this, some try to silence, oppress, deprive, and abuse them. Yet, they remain patient and persistent because "the keys to life" have been given to them alone, and they are indeed the best and most trustworthy guardians. Emily Daoud Nasrallah (Arabic: (3Eejdj OGhO fUQ Gddg(B), 1931-2018 was a Lebanese writer and women's rights activist.s
Arabic
Keywords: HQ1-2044 The Family. Marriage. Women- Feminism/Ecofeminism; Women's studies (3OQGSGJ GdfShjIs; Lebanon (3dHfGfs